The Effect of Tambora Leaf Extract (Ageratum conyzoides) on the Healing of Lacerated Wounds (Vulnus Laceratum) in Sprague Dawley Strain White Rats (Rattus norvegicus) - Nur Azizah Diah Pitriana; Nunung Herlina; Taufik Septiawan (CV. CENDIKIA JENIUS INDONESIA, 2025)
Vulnus laseratum is a condition where the continuity of tissue is disrupted and separated from normal tissue, usually due to tearing with significant force. Tambora leaves are known to contain secondary compounds such as terpenoids, alkaloids, essential oils, saponins, and phenols, which have various pharmacological activities. This study aims to evaluate the effect of Tambora leaf extract on the healing of torn wounds in white rats (Rattus norvegicus). The research method used was a true experimental method with a time series control group design. The research population consisted of four male white rats divided into four samples, including three treatment samples with Tambora leaf extract concentrations of 0.25%, 0.5%, and 1%, and one control sample using Bioplacenton ointment. The research results used a normality test (Shapiro Wilk) to analyze the data, with a p-value <0.05, which showed a result of 0.10, indicating that the data were normally distributed. It can be concluded that the concentration of P2 0.5% produces the optimal effect, better than the lower concentrations of Tambora leaf extract, and the 0.5% concentration results in the most effective hemostatic effect on wound healing. The suggestion from this study is to conduct clinical trials to evaluate the effectiveness of Tambora leaf extract (Ageratum Conyzoides) in the treatment of torn wounds (vulnus laseratum).